2020
DOI: 10.1108/ijrdm-09-2019-0305
|View full text |Cite
|
Sign up to set email alerts
|

Norms, consumer social responsibility and fair trade product purchase intention

Abstract: PurposeAlthough the relationships between subjective norms, personal norms, consumer social responsibility and consumer attitude have been studied, the direct or indirect relationships that potentially exist between these factors influencing consumer purchase intention remain unclear. Because attracting consumers to purchase fair trade (FT) products is fundamental to the success of the FT movement, the study introduced a theoretical framework that emphasizes the mediating role of personal norms and consumer at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 97 publications
3
33
0
1
Order By: Relevance
“…Additionally, our study highlights the effect of consumers’ environmentalism on the relationship between perceived supermarket ECSR and consumers’ attitudes towards the supermarket. This result extends previous knowledge on the impact of environmentalism on decisions related to products (Wang and Chou, 2021; Schill et al , 2019). Our data reveal that consumers who are highly concerned with environmental issues develop more favourable attitudes towards their supermarket when they perceive that it invests in ECSR than consumers who present little concern about environmental issues.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Additionally, our study highlights the effect of consumers’ environmentalism on the relationship between perceived supermarket ECSR and consumers’ attitudes towards the supermarket. This result extends previous knowledge on the impact of environmentalism on decisions related to products (Wang and Chou, 2021; Schill et al , 2019). Our data reveal that consumers who are highly concerned with environmental issues develop more favourable attitudes towards their supermarket when they perceive that it invests in ECSR than consumers who present little concern about environmental issues.…”
Section: Discussionsupporting
confidence: 87%
“…As such, previous research defines IJRDM 50,4 environmentalism as a general attitude or value orientation (Bamberg, 2003) that influences consumers' responses to products, such as purchase intentions (Kilbourne and Pickett, 2008;Schill et al, 2019). Past research has shown that consumers exhibiting stronger green attitudes and values are more likely to prefer environment-friendly products or environmental behaviours (Wang and Chou, 2021). In the case of person-organisation fit (P-O fit), the fit between the environmental values displayed by the organisation and those of the individual are likely to enhance individuals' preference for and commitment to the organisation (Kristof, 1996).…”
Section: The Moderating Effect Of Environmentalismmentioning
confidence: 99%
“…Articles linked to SDG 12 explore, for example, consumer understanding of the word sustainability (Barone et al, 2020), green product buying intentions (see D 'Souza et al, 2020;Stöckigt et al, 2018;Testa et al, 2018;Wang & Chou, 2020, among others) and consumer behavior (Principato et al, 2021). Health-related articles focus on health promotion and prevention (see Ficek & Novotný, 2019;Hu & Pratt, 2017).…”
Section: Consumer-level Interactions Between Marketing and Sdgsmentioning
confidence: 99%
“…Support services, support services in the form of customer service which is an element in a product strategy consisting of several supporting services that can be a small part or a large part of the overall product offering. (Cunningham and De Meyer-Heydenrych 2021;Faculty of Business, Economics and Accountancy, Universiti Malaysia Sabah, Kota Kinabalu, Malaysia et al 2021;Wang and Chou 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…So that with the fulfillment of needs and desires, consumer loyalty will be maintained. Maintained consumer loyalty is expected to increase the intensity of consumer purchases from time to time (Igir, Tampi, and Taroreh 2018;Iskamto, Ghazali, and Afthanorhan 2019;Wang and Chou 2020). Quality products have the possibility to be able to influence the intensity of buying behavior for a product, so having a product that is perceived as high quality means that the opportunity for consumers to choose is also higher.Quality products are produced from quality raw materials as well as qualified employees (Afthanorhan et al 2019;Basriani et al 2021;Dang, Nguyen, and Wang 2021).…”
Section: Introductionmentioning
confidence: 99%